T2 relaxometry of fetal brain structures using low‐field (0.55T) MRI - Payette, Kelly; Uus, Alena U.; Kollstad, Ella; Aviles Verdera, Jordina; Gallo, Dario; Hall, Megan; Hajnal, Joseph V.; Rutherford, Mary A.; Story, Lisa; Hutter, Jana (Magnetic resonance in medicine, 2025)
Purpose Human brain development during gestation is complex, as both structure and function are rapidly forming. Structural imaging methods using MRI are well developed to explore these changes, but functional imaging tools are lacking. Low‐field MRI is a promising modality to bridge this gap. The longer intrinsic T2* values at low field strengths increase the dynamic range and enable the quantification of individual brain regions with low T2* values, such as deep gray matter. This study investigates regional brain T2* quantification throughout the second half of gestation on low‐field 0.55T MRI. Methods Dynamic multi‐echo gradient‐echo sequences were acquired in 135 cases at 0.55 T between 20 and 40 weeks' gestation. Automatic high‐resolution reconstruction and segmentation tools were developed, resulting in T2* values of seven individual anatomical brain structures for each subject. These regional brain T2* values were analyzed throughout gestation. Results All regional fetal brain T2* values decreased throughout gestation (p < 0.01). Each anatomical brain structure had varying ranges and decay rates, with the cerebellum and white matter displaying the highest (nonfluid structure) values, with the maximum values between 350 and 400 ms at about 20 weeks. The brainstem and deep gray matter had the lowest range of T2* values, reaching values of 250 ms early in gestation. The matched volumetric assessment of the different structures demonstrated expected growth, matching current literature. Conclusion Low‐field MRI allows for a detailed, regional T2* analysis of the fetal brain, with more inclusive norms to be developed due to its wider bore.